The Anthropomorphic Representation of Masculine and Feminine Gender Semantics in English and Uzbek Phraseological Units (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the anthropomorphic representation of male and female figures in English and Uzbek phraseological units. It analyzes how idiomatic expressions reflect cultural perceptions of masculinity and femininity, highlighting the portrayal of men as strong and dominant, and women as nurturing and emotional, revealing how they reflect societal values and gender roles, offering insights into the intersection of language, culture, and gender.